La production de l’irresponsabilité juridique - Pascal Marichalar (Revue d'anthropologie des connaissances)
This text is a reply by the author to the reading by Stephane Le Lay of his book Qui a tué les verriers de Givors ? (Who Killed the Glassworkers of Givors?). The author underlines in particular the different apprehensions of the notion of responsibility, moral or legal, that coexist in an occupational setting.